The impact of the national school nutritional programme in the selected rural and urban primary schools in Mahwelereng circuit - Lebese, Mstenyeko Gladys; Ngobeni, Eliastsakane; Sepeng, Percy; Phage, Iitumeleng (International Journal of Business Strategy and Social Sciences, 2024)
This study evaluated the impact of the national school nutrition program IN the selected primary schools Mahwelereng circuit, Limpopo Province. To date, the (NSNP) reaches almost all schools in the poorest areas and quintiles nationwide. However, the COVID-19 pandemic has increased the demand on the National School Nutrition Program (NSNP) in schools far beyond expectation, even in schools outside quintile 1, 2, and 3. The purpose of this study was to investigate the impact of the NSNP in the primary schools in Mahwereleng Circuit, Limpopo Province. A qualitative phenomenological study within the interpretive research paradigm was used to explore the impact of the National School Nutrition Programme in primary schools. The researcher, through non-probability convenience sampling, selected a total of 12 primary school teachers from four primary schools in Mahwereleng Circuit. Data from semi-structured interviews was thematically analysed and interpreted to draw findings that answered the research questions. Findings indicated that the NSNP has a positive impact to learners’ welfare and academic performance in schools. The study appreciates the prescribed measures of food to each learner by the Department of Education (DoE). Primary school teachers in the selected schools around Mahwelereng circuit were interviewed individually for 20-30 minutes each in schools on the impact of the National School Nutrition Programme using semi-structured interviews to collect data. The implementation of the national school nutrition programme has a positive impact and established advantageous learning climate and decreased hunger and absenteeism in schools, while increasing enrolment, participation and scholarly execution among the schoolchildren.